Glomerular basement membrane damage in immunological glomerulonephritis - Hawkins, D. (1968)
Acute renal injury was induced immunologically with sheep antisera to rabbit glomerular basement membrane which were largely dependent on polymorphonuclear leucocytes (PMNs) for their pathogenic effect. This injury was characterized by the liberation of glomerular basement membrane material into the urine and a concomitant gross alteration in the permeability of the glomerular basement membrane. Selectivity of proteinuria was extremely low during PMN-mediated injury. These effects were eliminated by PMN depletion prior to the induction of experimental nephritis and were not observed when glomerular injury was induced by an antibody not significantly dependent upon PMNs. Of the known mediators of inflammation contained within PMNs, both acid proteases (cathepsins) and cationic proteins were found in the urines of rabbits with nephritis induced by a PMN-dependent antiserum.